Finite Element Analysis Of Bending Delamination In Multilayer Circuit Boards PCBs - Zulkifli, Ahmad Fazlullah (Universiti Sains Malaysia, 2022)
For decades, multilayer circuit boards have been often used in the electronic industry, and their application in electronic devices has been crucial and rising in recent years. It has the advantages of mobility, weight, and flexibility. Although the analysis of delamination bending has long existed, almost the research made is likely focusing on factor of temperature and pressure. Due to the importance of its functionality, it is crucial to understand and predict the failure analysis of its cohesive behaviour materials due to delamination bending. This paper is targeted to predict the delamination bending load of multilayer composite printed circuit board and to examine the effect of loading rate board stiffness on the crack path. From a simulation cohesive zone model (CZM) using ABAQUS software, the best methods of delamination modelling have been created to do analysis on the structure. This method using cohesive-zone approach and traction separation to model the mix bond made between cohesive prepreg and homogeneous material copper and substrate. In other to test the bending delamination, simulation done by using three different prepreg, difference PCBs stiffness and using impact load. The results showed that the difference type of test have difference impact on delamination strength and fracture. The structural analysis will be compared to get the best results. In conclusion, the simulation can basically improve knowledge about PCBs delamination, measure the force/load involved in PCBs and can compared the result in term of the stress field. In future work, there is a need to make more include in the simulation to make sure more flexible and best structure of PCBs.